Mechanical and electrical properties of ethylene-1-octene and polypropylene composites filled with carbon nanotubes. (28th July 2017) - Burmistrov, I.; Gorshkov, N.; Ilinykh, I.; Muratov, D.; Kolesnikov, E.; Yakovlev, E.; Mazov, I.; Issi, J.-P.; Kuznetsov, D.
Abstract: In the present work, the effect of carbon nanotubes (CNTs) addition on the electrical conductivity and mechanical properties of thermoplastic polymers was investigated. CNTs were incorporated into the polymer matrix either in high concentrations (masterbatch) or as an additive in small quantity (dilution source of masterbatches in a polymeric binder). Masterbatches containing a 5–20% by weight of CNTs and composites obtained through their addition in polypropylene - the actual content of CNTs in polymer 0.1 and 0.01 wt% - were synthesized and characterized by mechanical tests and scanning electron microscopy. Also, the frequency dependence of the AC electrical conductivity of masterbatches and dilute composites were measured. It has been shown that the introduction of masterbatches containing 10 wt% of CNT provides a more efficient reinforcement of the composite than those using masterbatches with 5 and 20 wt% of CNTs. It is also found that the alternating current (AC) conductivities display two or three regions: regions of constant conductivity and regions where the conductivity increases with increasing frequency (following the percolation scaling law). It was also observed that the conductivity increases drastically with increasing CNT content in the investigated concentration range (from 0 to 20 wt%).